2016
DOI: 10.1021/acs.energyfuels.5b02088
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Equilibrium of CO2 and CH4 and Their Mixture on Sichuan Basin Shale

Abstract: Adsorption equilibrium isotherms of CO2, CH4, and mixtures of CO2/CH4 on shale sampled from Nanchuan, southeastern Sichuan Basin, were measured at 278, 298, and 318 K by an accurate gravimetric method. The adsorption equilibrium data of CO2 and CH4 were fitted using both the virial model and the Brunauer–Emmett–Teller (BET) model, and the isotherms of CO2/CH4 mixtures were fitted by an extended BET model. On the basis of adsorption data, the adsorption selectivity factors for CO2 over CH4 (αCO2/CH4 ) and therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(88 citation statements)
references
References 39 publications
7
81
0
Order By: Relevance
“…[3] The primary reason for this is misinterpretation of isotherms measured in shale. Throughout the literature, isotherms measured for both hydrocarbons and gases, such as CO2, do not exhibit the distinct capillary condensation step defined in the IUPAC Type IV isotherm [4] or the continuous filling step that has recently been elucidated by Tan et al [5] and Barsotti et al [6] Instead, they appear similar to IUPAC Type I and II isotherms, [7], [8] which are attributed to mono-layer and multi-layer adsorption, respectively. [4] Therefore, they are given the same interpretation even though the IUPAC isotherms rely on fundamental assumptions about the adsorbate and adsorbent that are not true of shale rock.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The primary reason for this is misinterpretation of isotherms measured in shale. Throughout the literature, isotherms measured for both hydrocarbons and gases, such as CO2, do not exhibit the distinct capillary condensation step defined in the IUPAC Type IV isotherm [4] or the continuous filling step that has recently been elucidated by Tan et al [5] and Barsotti et al [6] Instead, they appear similar to IUPAC Type I and II isotherms, [7], [8] which are attributed to mono-layer and multi-layer adsorption, respectively. [4] Therefore, they are given the same interpretation even though the IUPAC isotherms rely on fundamental assumptions about the adsorbate and adsorbent that are not true of shale rock.…”
Section: Introductionmentioning
confidence: 99%
“…Gas injection is considered an effective way to enhance oil and gas recovery and it has been widely used worldwide [12,13]. According to the adsorption capacity difference between CO 2 and CH 4 on shale [14][15][16], using CO 2 displacement to enhance the shale gas recovery has become one of the most promoted ways [17][18][19]. As the insoluble organics in shale, MD method to choose carbon nanotubes in place of the shale organics.…”
Section: Introductionmentioning
confidence: 99%
“…Contributions on the behavior of confined fluids include adsorption equilibrium of CO 2 and CH 4 into different confined systems, such as shale. Duan et al (2016) studied the adsorption equilibrium isotherm data of CO 2 and CH 4 at 278, 298, and 318 K on rock samples from southeastern Sichuan Basin of China with a total organic carbon (TOC) of 2.58 wt%, inorganic components of quartz and orthoclase, and a wide pore size distribution. They demonstrated that the adsorption capacity of CO 2 is higher than that of CH 4 on shale.…”
Section: Methane-co 2 Replacement In Gas Hydratesmentioning
confidence: 99%